INVENTARISASI JENIS TANAMAN DI HUTAN TAMAN DIGULIS SEBAGAI SUMBER BELAJAR MATA KULIAH MEGABIODVERSITAS TROPIKA di PRODI BIOTEKNOLOGI ITEKES MU KALBAR - Nabila, Faika; Triwahyuni, Adelia; Fahira, Annisa Nasywa; Baihaqi, Muhammad Fiqri; Alang, Hasria (Guru Membangun, 2024)
Exploration is a mini form of research. The results of mini research can be used as teaching material. Exploratory activities will make a person more active and thorough. The aim of this research is to inventory the plants in the forest of Pontianak Digulis Park and conduct a literature study on the benefits of the plants found. Sampling was carried out observationally, and the type of research was descriptive. This research consists of two stages. The first stage of research includes identification using books of key determinations and benefits of plants found using literature studies. The second stage of research is analyzing its potential as teaching material or learning resource in the Megabiodiversity course. The research data was then documented and analyzed qualitatively. The results of the research found that there were 19 types of plants at the research location, namely durian, cengkodok, prawn pinch, banyan tree, orchid, bird's nest fern, mahogany, Bintangor, mangosteen, fern, banana tree, jampang, white teak, kekopian, hanjuang, red shoots, taro , fruit loh and laban. This type of plant has been widely studied and has a role. The role of the plants used indicates that the results of this research can be used as a learning resource in the Tropical Megabiodiversity course.